MULTI-OBJECTIVE COLLABORATIVE HARVEST WORKFORCE PLANNING FOR RICE SEED PRODUCTION CONSIDERING WORKLOAD BALANCE AND WORKER SATISFACTION - Thippo, Waranyoo; Jaturanonda, Chorkaew; Yaovasuwanchai, Sorawit; Khompatraporn, Charoenchai (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This paper proposes a collaborative harvest workforce (CHW) model that generates a worker-sharing schedule for farm owners tasked to produce rice seeds. The CHW model is a multi-objective optimization model with four objectives. The first two objectives are to minimize the average total cost and the number of harvesting days. The third objective is to minimize the difference in workloads, and the fourth is to maximize the workers’ total satisfaction. Farmlands were categorized into three difficulty levels with different satisfaction scores. The weighted sum and the weighted Tchebycheff methods were used to solve the CHW model, and the weights of the four objectives were computed based on expert opinions. All parties could benefit from this collaborative harvesting planning model and achieve sustainable relationships; farm owners could share costs and save harvesting time, while the workers could be more satisfied and reduce their risk of injury.